ANALISIS YURIDIS KEWENANGAN PPNS LINGKUNGAN HIDUP SEBAGAI PENYIDIK DENGAN TERKAIT PENGGABUNGAN KEMENTERIAN LINGKUNGAN HIDUP DENGAN KEMENTERIAN KEHUTANAN - Muhammad Reza Azhar; Alvi Syahrin; Suhaidi Suhaidi; Syamsul Arifin (Universitas Sumatera Utara, 2019)
ABSTRACT Lately the role of investigators is very important in the process of proof of law, especially with special criminal acts, especially criminal acts in the environmental field. therefore, it is deemed necessary to incorporate the Ministry of Environment and Forestry to the extent of the duties and authorities of environmental civil servant investigators in carrying out their duties and functions. Keywords : Investigators, Environment, authorities